Working toward a sustainable laboratory quality improvement programme through country ownership: Mozambique's SLMTA story - Jessina Masamha; Beth Skaggs; Isabel Pinto; Ana Paula Mandlaze; Carolina Simbine; Patrina Chongo; Leonardo de Sousa; Solon Kidane; Katy Yao; Elizabeth T. Luman; Eduardo Samogudo (AOSIS, 2014)
Background: Launched in 2009, the Strengthening Laboratory Management Toward Accreditation (SLMTA) programme has emerged as an innovative approach for the improvement of laboratory quality. In order to ensure sustainability, Mozambique embedded the SLMTA programme within the existing Ministry of Health (MOH) laboratory structure. Objective: This article outlines the steps followed to establish a national framework for quality improvement and embed the SLMTA programme within existing MOH laboratory systems. Methods: The MOH adopted SLMTA as the national laboratory quality improvement strategy, hired a dedicated coordinator and established a national laboratory quality technical working group comprising mostly personnel from key MOH departments. The working group developed an implementation framework for advocacy, training, mentorship, supervision and audits. Emphasis was placed on building local capacity for programme activities. After receiving training, a team of 25 implementers (18 from the MOH and sevenfrom partner organisations) conducted baseline audits (using the Stepwise Laboratory Quality Improvement Process Towards Accreditation [SLIPTA] checklist), workshops and site visits in six reference and two central hospital laboratories. Exit audits were conducted in six of the eight laboratories and their results are presented. Results: The six laboratories demonstrated substantial improvement in SLIPTA checklistscores; median scores increased from 35% at baseline to 57% at exit. It has been recommended that the National Tuberculosis Reference Laboratory apply for international accreditation. Conclusion: Successful implementation of SLMTA requires partnership between programme implementers, whilst effectiveness and long-term viability depend on country leadership, ownership and commitment. Integration of SLMTA into the existing MOH laboratory system will ensure durability beyond initial investments. The Mozambican model holds great promise that country leadership, ownership and institutionalisation can set the stage for programme success and sustainability.